(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
approaches are needed to reduce growth in blade mass with blade length. With design focus on turbine mass and cost for given performance, need arises for passive and active techniques to control the flow and the loads on the blades/turbine. To maximize the overall system benefits of these techniques, load control should be included from the onset. This research uses a optimization technique using the micro-tabs and different materials like Steel , aluminum , GFRP composites is used to reduce such weight. The well-defined model of wind blade is created and this will undergo for the analysis by ansys software, and the results will compare with that of basic materials like steel and existing design. Also to reduce the weight optimization via making ribsalso is used to modify the flow characteristics and can give the controlled flow of wind which in fact to increases the aerodynamic efficiency by means of composite materials. The thin airfoil blade is designed and performed with Ansys for the different materials. With prototype fabrication of the wind blade was carried out. Due to this smart material like glass fibre reinforced plastic with aluminum the rotor torque will increased. With this effect the overall wind mill performance will increase.